2021
DOI: 10.1108/ohi-07-2021-0157
|View full text |Cite
|
Sign up to set email alerts
|

A hierarchical definitional framework for a heterogeneous context: housing typologies in Tirana, Albania

Abstract: PurposeThe proposed definitional framework can be used to define housing typologies of cities in developing countries. It aims to define housing typologies in the capital city of Albania, Tirana, using the proposed hierarchical framework within the dynamics of four political periods: Ottoman, establishment, socialist and postsocialist.Design/methodology/approachThis study proposes a new definitional approach for the housing typologies through a hierarchical framework that defines the typologies based on their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…In the case of Tirana, the assimilation concerning mass housing typologies with a political period, particularly the Soviet Neoclassicist and legality statuses, highlight socioeconomic and cultural parameters within mass culture. These factors potentially formalized mass housing form, aesthetics, envelopes, and spatial attributes, justifying the polarity between the notion of homogeneity and heterogeneity (Manahasa et al, 2022). Indeed, the study by Sokienah (2021) revealed that this notion stirred an identity crisis in mass housing which emphasize a globalized image over local character due to the influence of economic and political globalization.…”
Section: Qualitative Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…In the case of Tirana, the assimilation concerning mass housing typologies with a political period, particularly the Soviet Neoclassicist and legality statuses, highlight socioeconomic and cultural parameters within mass culture. These factors potentially formalized mass housing form, aesthetics, envelopes, and spatial attributes, justifying the polarity between the notion of homogeneity and heterogeneity (Manahasa et al, 2022). Indeed, the study by Sokienah (2021) revealed that this notion stirred an identity crisis in mass housing which emphasize a globalized image over local character due to the influence of economic and political globalization.…”
Section: Qualitative Resultsmentioning
confidence: 98%
“…Theme 2: Dynamic Permeable Territory Although mass housing is defined through repetitive and standardized notions, Manahasa et al (2022) confirmed that it may be subjugated through a heterogenous context that is formed by the territorial interrelation of typological schemes and morphological patterns. In the case of Tirana, the assimilation concerning mass housing typologies with a political period, particularly the Soviet Neoclassicist and legality statuses, highlight socioeconomic and cultural parameters within mass culture.…”
Section: Qualitative Resultsmentioning
confidence: 99%
See 3 more Smart Citations